Working Toward Transformation and Change: Exploring Non-Aboriginal Teachers’ Experiences in Facilitating and Strengthening Students’ Awareness of Indigenous Knowledge and Aboriginal Perspectives - Burm, Sarah B (Scholarship@Western, 2012)
This study explores non-Aboriginal teachers’ accounts of ways in which they integrate Indigenous knowledge and perspectives into their teaching within the parameters set by the Ontario official curriculum. Ontario policy-makers and educational stakeholders have acknowledged the need to incorporate Aboriginal perspectives and content into curriculum and school communities, as reflected in documents such as the Ontario First Nation, Métis, and Inuit Education Policy Framework (2007). Nevertheless, non-Aboriginal educators continue to seek opportunities to advance professional growth and vocational clarity regarding their practice. Utilizing narrative inquiry within a case study approach, the study provides a space in which Aboriginal learners inform secondary school educators about their schooling experiences and discusses ways in which non-Aboriginal teachers approach the task of facilitating Aboriginal perspectives in the classroom. The findings indicate that non-Aboriginal secondary school educators are working to incorporate Indigenous knowledge into their pedagogical practice more now than in the recent past. Nevertheless both students and teachers are concerned with the overall reach and impact given its limited incorporation across subject areas other than history or social studies. More investment still needs to be made to ensure Indigenous knowledge and its pedagogies both in a local and broader context are identified as a valuable knowledge system.